Adaptation of plant‐mycorrhizal interactions to moisture availability in prairie restoration. Issue 1 (28th September 2020) - Lubin, Terra K.; Alexander, Helen M.; Bever, James D.
Abstract : The strength and direction of plant response to inoculation with arbuscular mycorrhizal fungi (AM fungi) is dependent on both abiotic and biotic contexts, often generating patterns of AM fungal mediation of plant adaptation. However, knowledge of plant‐community level effects of these interactions in grassland restoration is limited. We conducted a field inoculation experiment by inoculating five plant species native to a drier prairie and five plant species native to a moister prairie with mycorrhizal fungal communities from each prairie type. Species were paired by genus or family to account for phylogenetic effects. The inoculated plants were transplanted to study plots seeded with a restoration seed mix. Plots were manipulated to create either moister or drier conditions similar to environments of the plant species and mycorrhizal communities. In both transplanted and seeded plant species, we found that only drier prairie‐range species benefited from moisture‐regime matched AM fungal inoculum. Other seeded prairie plant species demonstrated a negative response to inoculation, likely due to the earlier successional stage of these species. Additionally, nonseeded plants benefited from inoculation in different ways: native nonseeded plants had highest cover with drier prairie inoculum in drier conditions, while nonnative plants had highest cover with moister prairie‐origin inoculum. These results suggest that use of local AM fungi may be particularly important in restorations at drier sites, even at relatively small differences in moisture availability. Further, specific knowledge of relative responsiveness of seeded plant species and nonseeded plant species to AM fungal inoculation will be useful in planning restorations.